AN ANALYSIS OF NEWS ITEM IN SENIOR HIGH SCHOOL TEXTBOOK USING TRANSITIVITY SYSTEM - Agung Setiyono, - (2018)
Textbook plays an important role in the field of education. Moreover, in some schools, teachers rely heavily on textbook to establish and to formulate the course based on the content of textbook. This issue leads the researcher to conduct a research about the content of textbook. The research was aimed at finding out to what extent the news item texts in senior high school textbook meet the characteristics of the news item text in terms of significant lexicogrammatical features; and what process types are employed in news item texts in senior high school textbook. The qualitative case study with document analysis technique was employed as the study method. The data were obtained from five news item texts in one of textbooks for grade XII. To analyze the data, Systemic Functional Linguistics (SFL) framework especially transitivity analysis was employed. The result revealed that two out of five news item texts in senior high school textbook fully met the characteristics of significant lexicogrammatical features. Meanwhile, two texts were found using material passive clause and one text is found using indirect verbal clause that were inappropriate in news item text. In addition, five process types were employed in news item text, existential, material, mental, relational, and verbal process. From these process types, three types, material, relational, and verbal process, played a significant and important role in news item. ;---Buku Teks memainkan peran yang penting dalam dunia pendidikan. Bahkan, di beberapa sekolah, guru sangat bergantung terhadap buku teks untuk membuat dan menyusun materi bahan ajar berdasarkan dari isi buku teks. Hal ini melatarbelakangi penulis untuk melaksanakan penelitian mengenai isi buku teks. Penelitian ini bertujuan untuk mengetahui dalam hal apa saja teks berita dari suatu buku teks memenuhi kriteria teks berita berdasarkan ciri kebahasaannya dan tipe kata kerja apa saja yang digunakan dalam teks berita. Penelitian ini menerapkan studi kasus kualitatif dengan analisa dokumen. Data diperoleh dari lima teks berita dalam salah satu buku teks untuk kelas XII. Kerangka Linguistik Fungsional Sistemik khususnya analisis transitif diterapkan dalam menganalisa data. Penelitian ini menunjukan bahwa dua dari lima teks berita memenuhi kriteria ciri kebahasaan suatu teks berita. Sementara, dalam dua teks lainnya ditemukan penggunaan kalimat pasif dan satu teks ditemukan penggunaan kalimat tidak langsung yang dianggap tidak sesuai kaidah kebahasaan teks berita. Kemudian, ditemukan bahwa terdapat lima tipe kata kerja dalam teks berita, eksistential, mental, material, verba, dan relasional. Dari tipe kata kerja tersebut, tiga tipe yaitu material, verba, dan relational memiliki peran yang signifikan dan dominan dalam teks berita.